STUDI KASUS: ANEMIA RINGAN PADA KEHAMILAN TRIMESTER III - Rosita Fowor; Vina Dwi Wahyunita (Jurnal Kebidanan, 2021)
Anemia is a condition which the body lacks red blood cells (erythrocytes) in the blood so that the tissue lacks oxygen. Anemia of pregnancy or so called potential danger to mother and child is very dangerous for mother and child is very dangerous for mother and child, so anemia in pregnancy becomes a serious problem. Gravida, age, parity, education level, economic status and adherence to consuming Fe tablets or blood boosters are the causes of anemia during pregnancy. This case study describes mild anemia in pregnancy experienced by a 26 years old multigravida pregnant women who was pregnant with her fourth child with close pregnancy intervals. The care provided for this problem is by offering Fe tablets and vitamin C supplements during pregnancy, as well as education on the consumption of nutritious foods that contain iron.